Changes in fish composition before and after Dau Tieng lake construction - Tam, Tong Xuan; Duc, Nguyen Huu (Academia Journal of Biology, 2014)
Dau Tieng Lake (high water of Sai Gon river) is located at Tan Chau and Duong Minh Chau district (Tay Ninh province), Dau Tieng district (Binh Duong province), Binh Long district (Binh Phuoc province); V-shaped, elevated northward; 11029’07’’-11036’15’’ north latitude and 106010’49’’-106029’07’’est longitude; 25 km east west of Tay Ninh town and 70 km north of Hochiminh city. It’s the largest irrigation system in Vietnam with and area of 270 km2, water area of 27.000 ha (5.000 ha of semidiurnal tide land), about 1,45-1,5 billion m3 of water irrigating 175.000 ha of agricultural land. The lake was built in August 1981 and put in operation in January 1985. Since its construction, there have been several researches showing the impact of damming on hydrologic data (rate of flow, water volume, salinity…), interrupting fish migration and affecting their lives. In recent years, fish being caught with high frequency, in many forms (fishing even newborns and breeding ones…) together with polluted water have upset the fish composition comparing with the moment before the lake was built [2, 8, 10, 12]. Dau Tieng lake was completely constructed in January 1985 from the high water of Sai Gon river. As a result, the previous fish composition belongs to the rich river fish fauna, with some local species and some brackish water migrating from the sea. After the lake construction, the fish fauna has changed from river fish species to lake one with many characteristic species. This change lead to the disappearance of some species and appearance of new ones representing the lake ecosystem. Before the lake construction (January 1985), Le Hoang Yen et al (1979 - 1981) discovered 83 species belonging to 49 genera, 25 families, 9 orders. After the lake formation, our research and others’ (1998 - 2009) discovered 123 species, 71 genera, 28 families, 10 orders. While 54 new species appear, 14 disappeared. That means there has been 40 species more (32.52% more), 22 genera (30.99%), 3 families (10.71%) and 1 order (10,00%). So, the big change in fish species composition before and after the lake formation is due to many impact factors. 14 disappeared species being brackish ones and could not adapt to the fresh water environment after the lake construction. Before the lake construction, salinity was from 1 - 2‰ (dry season) and 0.1 - 0.2‰ (rain season) [8], it showed that Dau Tieng lake’s water used to be brackish during the dry season. Our research in 2007 showed that salinity ranges from 0.29‰ (dry season) to 0.35‰ (rain season), that means after the lake formation, Dau Tieng’s water was completely fresh (0 ≤ water salinity ≤ 1 ‰). Favoring strong water flow in the high water, these fish’s lives have been upset by the lake damming which caused hydrologic changes (rate of water flow, water volume…). Besides, our research and others’ (2007) showed that Dau Tieng’s water is not alumed or salivated but only reaches B level for surface water quality and irrigation water quality, not reaching the standards for water life protection (TCVN 6774 - 2000), in the a mesosaprobe infection category (water level of 3/6) and there are signs of moving to b mesosaprobe infection category (water level of 4/6). On the other hand, these fish have been unreasonably over caught by local fishermen due to their high economic value, catching even juveniles and breeding ones… These are the reasons for their disappearance from the lake. The new 54 species after the lake formation may be not all for Dau Tieng lake because the earlier researchers collected data in 3 years, possibly missing some. Out of 19 species are from immigration (15.48%), there are 14 new species (11.38%) brought in the process of fish caging in the lake or from local fish ponds or raised by Tay Ninh Marine Product Company and Dau Tieng Irrigation Company to purify lake water and create fish sources for local people’s catching. The new fish species after the lake formation are typically interior field ones, preferring still and fresh water. Some of them are raised locally, some come from the neighboring lakes and ponds. This increase is also due to fish coming from high water’s rivers and creeks. Besides, the sea and brackish water species have adapted to fresh water environment and flourish in the lake. 2 species are in Vietnam’s Red Book (2007). 39 species (31.71%) are going down rapidly in number and need special protection. Some have gone down dramatically in number and may not be in Dau Tieng Lake in the next few years if strict protection policies are not applied.